Predictors of posttraumatic stress and preferred sources of social support among Canadian paramedics. Issue 3 (1st September 2015) - Donnelly, Elizabeth A.; Bradford, Paul; Davis, Matthew; Hedges, Cathie; Klingel, Michelle
Abstract: Objective: Emergency medical service (EMS) providers are exposed to a variety of stressors endemic to the profession. These exposures may contribute to stress reactions, including posttraumatic stress. The objective of this study was to evaluate the relationship between work-related stressors and posttraumatic stress. The secondary objective was to determine paramedics' preferred sources of support for managing work-related stress. Methods: 269 paramedics in a county-based EMS service were invited to complete an online survey. Respondents reported their demographic characteristics, levels of chronic stress, critical incident stress, posttraumatic stress symptomatology (PTSS), and preferred sources of support for managing work-related stress. Results: A total of 145 paramedics completed the survey. PTSS was significantly correlated with operational stress ( p <0.001), organizational stress ( p <0.001), and critical incident stress ( p <0.001). Regression models revealed that chronic operational stress was a significant independent predictor of PTSS ( p <0.001) and in combination with critical incident stress ( p <0.01). Paramedics reported a higher preference for receiving support from a work partner, friend, or family member than from other sources ( p <0.001). Conclusion: Both chronic and critical incident stressors appear to be significant predictors of PTSS. Our findings suggests that holistic health and wellness initiatives that address the impact of both critical incident stress and the chronic stressors associated with day-to-day operations may help mitigate PTSS. Our findings also provide preliminary evidence that interventions may benefit from a focus on peer support and on friends and family members who can support the affected paramedic. RÉSUMÉ: Objectifs: Les fournisseurs de soins médicaux d'urgence (SMU) sont exposés à une multitude de facteurs de stress qu'on pourrait qualifier d'« endémiques » à la profession. L'exposition à ces facteurs peut engendrer des réactions de stress, y compris l'état de stress post-traumatique (ESPT). L'étude avait pour objectif principal d'évaluer le lien entre les facteurs de stress liés au travail et l'état de stress post-traumatique et, pour objectif secondaire, de déterminer les sources préférées de soutien des ambulanciers paramédicaux pour faire face au stress lié au travail. Méthode: Des ambulanciers paramédicaux, au nombre de 269, travaillant pour un fournisseur de SMU dans un comté ont été invités à répondre à une enquête en ligne. Les répondants ont fait état de leurs caractéristiques démographiques, du degré de stress chronique, d'événements traumatisants, de symptômes d'état de stress post-traumatique ainsi que de leurs sources préférées de soutien pour faire face au stress lié au travail. Résultats: Au total, 145 ambulanciers paramédicaux ont répondu à l'enquête. L'ESPT était en corrélation étroite avec le stress lié au fonctionnement ( p <0, 001), le stress lié à l'organisation ( p <0, 001) et le stress lié à des événements traumatisants ( p <0, 001). Les modèles de régression ont révélé que le stress chronique, lié au fonctionnement était un facteur prévisionnel important et indépendant d'ESPT ( p <0, 001), de même que l'association du stress lié au fonctionnement et du stress lié à un événement traumatisant ( p <0, 01). Les ambulanciers paramédicaux ont indiqué qu'ils préféraient recevoir le soutien de collègues, d'amis ou de membres de la famille que celui d'autres sources ( p <0, 001). Conclusions: Le stress chronique et le stress lié à des événements traumatisants semblent des facteurs prévisionnels importants d'ESPT. D'après les résultats de l'étude, des initiatives de santé globale et de mieux-être ayant pour cibles l'effet du stress lié à des événements traumatisants et les facteurs de stress chronique, liés au fonctionnement quotidien pourraient atténuer l'ESPT. De plus, l'étude fournit des données préliminaires selon lesquelles on gagnerait à élaborer des interventions fondées sur le soutien de collègues, d'amis ou de membres de la famille capables d'aider l'ambulancier paramédical affecté.